Bridging fictional game guides and imaginary games - Tim Timvig; Carl-Erik Engqvist; Karin Danielsson (Eludamos)
This article proposes a widened view of fictional games by considering the game guidebook Vermis I – Lost Dungeons and Forbidden Woods (2023) by Plastiboo. Through a kaleidoscope of theoretical concepts hailing from playfulness, aesthetics, design, narratology, and literary reception, the authors engage with the issues of literary play and imaginary games. This conclusion is drawn: Vermis exemplifies a fictional game existing both parallel to a secondary world and within its own secondary world created by a factual book. Its format invites a literary play activity showcasing the playful power inherent in fictional games.